Social Security Guide : The White Paper and the Beveridge Report Compared - Great Britain. Office of the Minister of Reconstruction. Social insurance ; Great Britain. Inter-departmental Committee on Social Insurance and Allied Services. Social insurance and allied services ; Beveridge, William Henry Beveridge, Baron, 1879-1963; Clarke, Joan Simeon (London : The Social Security League)
1944-10-01 1944 1940s 20 pages SOCHAL SECURITY GUIDE THE WHITE PAPER AND THE BEVERIDGE REPORT COMPARED "Freedom from want cannot be forced on a democracy or given to a democracy. It must be won by them. Winning it needs courage and faith and a sense of national unity." BEVERIDGE REPORT 6D Published by THE SOCIAL SECURITY LEAGUE, 33 BRUTON STREET, LONDON, W.1. 15X/2/453/3